STUDY OF PRESSURE FLUCTUATIONS CREATED BY A HYDRODYNAMIC CAVITATOR - Yakymechko, Yaroslav (Sworld-Us Conference proceedings, 2023)
Experimental study of the hydrodynamic cavitator and its influence on the parameters of oil Dolinskogo field has been performed. The studies were conducted on the basis of Oil and Gas Management "Dolinanaftogaz" on the developed program and methodology i